Efektivitas Desain Rumah Deret Perbaikan Lingkungan Permukiman Manggarai Berdasarkan Arsitektur Perilaku - irine nur sabrina kusuma; Budi Sudarwanto (Jurnal Arsitektur ARCADE, 2025)
Abstract: Urbanization with unbalanced population and economic growth is the main factor of slums creation. These slums are characterized by inadequate provision of basic infrastructure and public services, and must be improved. Through the housing and infrastructure and utility improvement program, the Government expects improvements, construction of habitable houses in the form of row houses, by arranging the order of buildings and the environment. The target is the indicative location of Manggarai Jakarta, which is generally known as an area that mostly doesn’t meet the indicators of a habitable house and is located in a densely populated slum area. In order for the improvement program to run effectively, the design needs to be adjusted to the behavior and identity of its residents. This study aim of identifying attributes that affect the comfort of housing. Using a qualitative approach to the behavioral setting architectural method, this study maps the activities of residents in their homes and their environment, allowing visualization of resident behavior patterns with spatial functions, design, and environmental atmosphere. The results of this study are expected to provide recommendations for residential designs that create a more humane, healthier, more conducive and effective residential environment, and able to answer the problems of slums in Manggarai, also contribute to development of architectural science, especially the row housing designs. Keyword: Row House Housing, Spatial Planning, Behavioral Architecture, Manggarai Jakarta Settlement Abstrak: Urbanisasi dengan perkembangan jumlah penduduk dan ekonomi tak seimbang menjadi faktor utama terciptanya permukiman kumuh. Permukiman kumuh ini ditandai dengan tidak memadainya penyediaan infrastruktur dasar, juga layanan publik, dan harus dibenahi. Melalui program perbaikan rumah dan prasarana sarana dan utilitas, Pemerintah mengharapkan perbaikan, pembangunan rumah layak huni berupa rumah deret, dengan menata keteraturan bangunan dan lingkungan. Sasarannya pada lokasi indikatif Manggarai Jakarta yang secara umum area ini dikenal mayoritas tidak memenuhi indikator Rumah Layak Huni dan berada pada kawasan permukiman kumuh padat penduduk. Agar program pembenahan berjalan efektif, desain hunian perlu menyesuaikan dengan perilaku serta identitas warganya. Penelitian ini bertujuan untuk mengidentifikasi atribut yang mempengaruhi kenyamanan hunian. Menggunakan pendekatan kualitatif metode arsitektur setting perilaku, penelitian ini memetakan aktivitas warga dalam hunian serta lingkungannya, memungkinkan visualisasi pola perilaku warga dengan fungsi ruang, desain, dan lingkungan. Hasil penelitian ini diharapkan dapat memberikan rekomendasi desain hunian yang menciptakan lingkungan permukiman yang lebih manusiawi, menjadi lebih sehat, kondusif juga efektif, dan mampu menjawab permasalahan permukiman kumuh di Manggarai, juga dapat berkontribusi pada pengembangan ilmu pengetahuan arsitektur, terutama pengembangan desain hunian permukiman deret. Kata Kunci: Hunian Rumah Deret, Tata Ruang, Arsitektur Perilaku, Permukiman Manggarai Jakarta